LNG mass flowrate measurement using Coriolis flowmeters: Analysis of the measurement uncertainties. (June 2021) - Wu, Thomas Y.; Kenbar, Asaad; Pruysen, Aart
Highlights: The uncertainty of Coriolis mass flowmeter (CMF) is investigated for LNG mass flow measurement. Expanded uncertainty of measured Young's modulus of stainless steel 316 is evaluated to be 1.90%. Expanded uncertainty of corrected Young's modulus at LNG temperature (120 K) is 0.47%. Uncertainties due to thermal expansion, pressure, temperature, zero stability and repeatability are evaluated for CMF. Expanded uncertainty for LNG mass flow measurement using a CMF is estimated to be 0.50%. Abstract: The uncertainty of Coriolis mass flowmeter (CMF) has been investigated for liquefied natural gas (LNG) mass flowrate measurement. The expanded uncertainty of the Young's modulus of stainless steel 316 measured by NIST is evaluated to be 1.90%, taking into consideration the lot-to-lot variability of the material. We have shown that the corrected Young's modulus value at cryogenic temperature (120 K) has a smaller expanded uncertainty of 0.47%, through calibration of the CMF using traceable water calibration facility and a correction term to compensate the Young's modulus change from ambient to cryogenic temperature of 120 K. We have evaluated other mass flowrate measurement uncertainty factors including thermal expansion, pressure correction effect, temperature measurement, zero stability and meter repeatability. The expanded uncertainty of a CMF for LNG flowrate measurement is estimated to be 0.50% with the uncertainty coverage factor k  = 2. The dominating component is from the uncertainty of the corrected Young's modulus for stainless steel at cryogenic temperature. This uncertainty analysis shows that a CMF can provide very accurate mass flowrate measurement for LNG custody transfer.